A toponímia literária em Rua do Siriri, de Amando Fontes - Pereira, Marcos José Santos (2025)
This dissertation investigates linguistic-literary and extralinguistic elements based on the place names listed in the fictional novel Rua do Siriri, by Amando Fontes, published in 1937. This study applies the theoretical and methodological foundations of Literary Onomastics. After the selection and lexicographic treatment of street, avenues, squares, and neighborhoods toponyms, it relates these lexical items to the description of the city of Aracaju in the first half of the 20th century. To achieve this objective, a literature review was carried out on Literary Onomastics, especially in Brazil, guided by the keywords literary onomastics, toponymy, literature, and memory, in academic databases from 1990 to the present time. We registered the data in lexicographic-toponymic forms, included in the Appendix, and we compared the corpus extracted from the work with maps of the city of Aracaju dating from the second half of the 19th century, such as the list of names in the Catalog of Public Places in the Municipality of Aracaju. As for the analysis, we pointed out the main functions of these toponyms in the book, as a result, it was possible to prove that these placenames extracted from Fontes's have a realistic character and may, in a semantic-etymological analysis of the literary, mimetic and memorialist functions, identify a high degree of verisimilitude.